Enzyme-linked immunosorbent assay for detection of Mycobacterium bovis antibodies in cattle - GUPTA, V K; RAM, G C (The Indian Journal of Animal Sciences, 2013)
The major and general problem in serodiagnosis of bovine tuberculosis is the grade of specificity of the test. Lack of specificity of bovine PPD caused unacceptable number of the false positive results. In this study the usefulness of enzyme linked immunosorbent assay (ELISA) for the diagnosis of bovine tuberculosis is further evaluated. A total of 102 cows (50 from lzatnagar farm and 52 from Pantnagar farm). were tested for the presence of anti Mycobacterium bovis antibodies in their sera. Bovine PPD and M. bovis specific glycolipid neoantigen (MB-O-BSA) were used as antigens in ELISA. The percentages of seropositive animals were 94% and 100% with bovine PPD in Izatnager and Pantnagar, whereas only 50% and 82.6% animals reacted to neoantigen in ELISA in both the farms respectively. It was observed that use of speciesspecitic antigens in ELISA may reduce the number of false reactor and revolutionize the serodiagnosis of tuberculosis in cattles.